Cultural Taboos, "Mystical Practices" and Perceived Business Performances in the Informal Sector: An Exploration of Bayam-Sellams in African Local Markets - Pierre, Emmanuel Ndebi; Jean-Hubert, Etoundi (Archives of Business Research, 2024)
The objective of this article is to highlight the reality of unorthodox commercial practices in markets, by local vendors of the informal sector in Africa. An in-depth analysis of a sample of twenty-four (24) petty traders reveals that these traders use both common sense, by developing proximity to their market, and the mystical dimension of their cultural era, to achieve their commercial performance objectives. In so doing, they perceive this mystical dimension as being effective in attracting customers, building customer loyalty and making their business more competitive.